Stunting and Cognitive Develompent of Children Aged 2-5 Years - Lantara, Andi Millaty Halifah Dirgahayu; Sangkal, Andini; Latief, Shofiyah; Darma, Sidrah; Bakhtiar, Ilma Khaerina Amaliyah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Insufficient nutritional intake from the beginning of pregnancy until the first two years of life has a significant effect on the child's growth and development process, such as stunting. Stunting is the condition of a child having a length or height that is lower or less than his age and has a value < -2 standard deviation. Malnutrition in children can inhibit the formation of brain cells resulting in changes to the structure and function of the brain itself. This will then have an impact on the child's cognitive development. The research aims to determine the relationship between stunting and cognitive development in children aged 2-5 years. The sample used in this research was toddlers aged 2-5 years, totaling 38 children. The research design used was cross-sectional (cross sectional study). Data were analyzed using the Somers'D statistical test. The research results found a relationship between stunting and cognitive development in children aged 2-5 years. The conclusion is that children who experience stunting will cause their cognitive abilities to decline.